The TALE never ends: A comprehensive overview of the role of PBX1, a TALE transcription factor, in human developmental defects. Issue 9 (18th May 2022) - Mary, Laura; Leclerc, Delphine; Gilot, David; Belaud‐Rotureau, Marc‐Antoine; Jaillard, Sylvie
Abstract: PBX1 is a highly conserved atypical homeodomain transcription factor (TF) belonging to the TALE (three amino acid loop extension) family. Dimerized with other TALE proteins, it can interact with numerous partners and reach dozens of regulating sequences, suggesting its role as a pioneer factor. PBX1 is expressed throughout the embryonic stages (as early as the blastula stage) in vertebrates. In human, PBX1 germline variations are linked to syndromic renal anomalies (CAKUTHED). In this review, we summarized available data on PBX1 functions, PBX1‐deficient animal models, and PBX1 germline variations in humans. Two types of genetic alterations were identified in PBX1 gene. PBX1 missense variations generate a severe phenotype including lung hypoplasia, cardiac malformations, and sexual development defects (DSDs). Conversely, truncating variants generate milder phenotypes (mainly cryptorchidism and deafness). We suggest that defects in PBX1 interactions with various partners, including proteins from the HOX (HOXA7, HOXA10, etc.), WNT (WNT9B, WNT3), and Polycomb (BMI1, EED) families are responsible for abnormal proliferation and differentiation of the embryonic mesenchyme. These alterations could explain most of the defects observed in humans. However, some phenotype variability (especially DSDs) remains poorly understood. Further studies are needed to explore the TALE family in greater depth.